INTEGRATION OF GREEN ECONOMY POLICIES IN POST-PANDEMIC ECONOMIC RECOVERY: OPPORTUNITIES AND CHALLENGES - Jusmarni Jusmarni; Reina A. Hadikusumo (CV. Adiba Aisha Amira, 2025)
The post-pandemic economic recovery presents a strategic opportunity to integrate green economy policies to create more sustainable and inclusive growth. These policies involve measures such as renewable energy development, resource efficiency and carbon emission reduction that can strengthen economic resilience while protecting the environment. However, their implementation faces various challenges, including high start-up costs, resistance from conventional industries, and technological and infrastructure limitations in some countries. This article examines the opportunities offered by green economy policy integration as well as the challenges that need to be overcome in the post-pandemic economic recovery process. Thus, with a collaborative approach and strategic policies, the green economy can be a key solution to realising a sustainable global economic recovery and supporting long-term development.